CEP192 is a novel prognostic marker and correlates with the immune microenvironment in hepatocellular carcinoma - Liu, Yanli; Liang, Wanmei; Chang, Yabin; He, Zehui; Wu, Meijian; Zheng, Haozhi; Ke, Xinrong; Lv, Minjia; Liu, Qingqian; Liu, Qinyu; Tang, Waner; Huang, Qiaoling; et al. (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) responds poorly to standard chemotherapy or targeted therapy; hence, exploration for novel therapeutic targets is urgently needed. CEP192 protein is indispensable for centrosome amplification, which has been extensively characterized in both hematological malignancies and solid tumours. Here, we combined bioinformatics and experimental approaches to assess the potential of CEP192 as a prognostic and therapeutic target in HCC. CEP192 expression increased with tumour stage and was associated with poor clinicopathologic features, frequent recurrence, and higher mortality. Upon single-cell RNA sequencing, CEP192 was found to be involved in the proliferation and self-renewal of hepatic progenitor-like cells. This observation was further evidenced using CEP192 silencing, which prevented tumour cell proliferation and self-renewal by arresting cells in the G0/G1 phase of the cell cycle. Notably, CEP192 was highly correlated with multiple tumour-associated cytokine ligand-receptor axes, including IL11-IL11RA, IL6-IL6R, and IL13-IL13RA1, which could promote interactions between hepatic progenitor-like cells, PLVAP+ endothelial cells, tumour-associated macrophages, and CD4+ T cells. Consequently, CEP192 expression was closely associated with an immunosuppressive tumour microenvironment and low immunophenoscores, making it a potential predictor of response to immune checkpoint inhibitors. Taken together, our results unravel a novel onco-immunology role of CEP192 in establishing the immunosuppressive tumour microenvironment and provide a novel biomarker, as well as a potential target for therapeutic intervention of HCC.